Sport-related concussion attitudes and knowledge in elite English female footballers - Shafik, A.; Bennett, P.; Rosenbloom, C.; Kryger, K. O.; Carmody, S.; Power, J. (Science and Medicine in Football, 2024)
Background: Sport-related concussions (SRC) are more common and more severe in women`s football than men`s yet the knowledge and attitudes of SRC in the women`s game are not well understood. The objective of this study was to assess the SRC knowledge and attitude in elite female footballers. Methods: An online questionnaire was sent to all registered players in the English Football Association Women`s Super League (WSL) and Championship. Respondents completed an amended version of the Rosenbaum Concussion Knowledge and Attitudes Survey (RoCKAS). Concussion Knowledge Index (CKI) and Concussion Attitudes Index (CAI) scores were derived for all respondents. Results: One hundred and twenty-three players completed the survey with 111 fitting the inclusion criteria. The mean CKI score was 20.5 ± 2.3 and the mean CAI score was 63.3 ± 6.3. A weak positive correlation was shown between the CKI and CAI (r = 0.20; p = 0.03). Previous concussion education had a significant impact on increased knowledge (U = 1198; p = 0.04). There was no significant difference in concussion attitudes and knowledge between the WSL and Championship or in those with a previous concussion history and no previous concussion (p > 0.05). Conclusion: Previous SRC education demonstrated an increased knowledge around concussion but a limited impact towards concussion attitudes. It is suggested that concussion education should be mandated across the professional game to enhance player welfare.